A new genus of mellitid sand dollar (Echinoidea: Mellitidae) from the eastern Pacific coast of the Americas - Coppard, Simon E. (Zootaxa, 2016)
Lanthonia gen. nov. Coppard 2016 is a genus of clypeasteroid sand dollar whose members inhabit shallow, sandy waters from Mexico (including the Gulf of California) to Colombia in the tropical and subtropical eastern Pacific. Lanthonia includes Lanthonia longifissa (Michelin, 1858) and Lanthonia grantii (Mortensen, 1948), with L. longifissa hereby designated as the type species. Both L. longifissa and L. grantii were previously placed in the genus Mellita (L. Agassiz, 1841). However, levels of genetic divergence between a lineage containing L. longifissa and L. grantii and a lineage containing all other species of Mellita, including the type species M. quinquiesperforata (Leske, 1778), indicate genus level differentiation. The systematic interpretation of this group also supports the designation of this new genus as it allows the tree topology to be recovered from the nomenclature and clarifies the historical biogeography of these clades. This has resulted in members of both lineages today being sympatric in the eastern Pacific. Members of Lanthonia are morphologically differentiated from the type species of Mellita and all Pacific Mellita in having very narrow ambulacral regions between the food grooves and the ambulacral lunules on the oral surface, these being very broad in both M. quinquiesperforata and M. notabilis. The dentation of the bidentate pedicellariae also differentiate these genera, with small peripheral teeth present along the edge of the blade in species of Lanthonia and one to three enlarged intersecting teeth present distally in all species of Mellita.